Infrared observations of Jovian aurora from Juno's first orbits: Main oval and satellite footprints. Issue 11 (3rd June 2017) - Mura, A.; Adriani, A.; Altieri, F.; Connerney, J. E. P.; Bolton, S. J.; Moriconi, M. L.; Gérard, J.‐C.; Kurth, W. S.; Dinelli, B. M.; Fabiano, F.; Tosi, F.; Atreya, S. K.; et al.
Abstract: The Jovian Infrared Auroral Mapper (JIRAM) is an imager/spectrometer on board NASA/Juno mission for the study of the Jovian aurorae. The first results of JIRAM's imager channel observations of the H3 + infrared emission, collected around the first Juno perijove, provide excellent spatial and temporal distribution of the Jovian aurorae, and show the morphology of the main ovals, the polar regions, and the footprints of Io, Europa and Ganymede. The extended Io "tail" persists for 3 h after the passage of the satellite flux tube. Multi‐arc structures of varied spatial extent appear in both main auroral ovals. Inside the main ovals, intense, localized emissions are observed. In the southern aurora, an evident circular region of strong depletion of H3 + emissions is partially surrounded by an intense emission arc. The southern aurora is brighter than the north one in these observations. Similar, probably conjugate emission patterns are distinguishable in both polar regions. Key Points: Detailed observation of a very long tail of the Io magnetic footprint Identification of thin multiple arc structures in the northern and southern ovals, and of bright spots and depletion in the south pole Filamentation of alternatively upward and downward current in the 0°–90° SIII sector in the north